2018
DOI: 10.1111/ijpo.12436
|View full text |Cite
|
Sign up to set email alerts
|

Increased brain and behavioural susceptibility to portion size in children with loss of control eating

Abstract: Children who reported LOC were more susceptible to the PSE and showed alterations in food-cue processing in the cerebellum, a hindbrain region implicated in satiety signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…These heightened expectations may also be maintained and exacerbated by elevated taste responsiveness, which may initiate a vicious cycle that elevates risk for disinhibited eating behaviors, such as LOC eating (Berridge, 2009). Supporting this notion are findings showing that children with LOC eating exhibit greater neural activation to highly palatable food cues compared with children without LOC eating (English et al, 2019). A number of other reward-based constructs, such as the reinforcing value of food and food addiction, warrant study in relation to LOC eating to elucidate which youth may be predisposed to develop adult BED and obesity.…”
Section: Reward Responsivitymentioning
confidence: 99%
“…These heightened expectations may also be maintained and exacerbated by elevated taste responsiveness, which may initiate a vicious cycle that elevates risk for disinhibited eating behaviors, such as LOC eating (Berridge, 2009). Supporting this notion are findings showing that children with LOC eating exhibit greater neural activation to highly palatable food cues compared with children without LOC eating (English et al, 2019). A number of other reward-based constructs, such as the reinforcing value of food and food addiction, warrant study in relation to LOC eating to elucidate which youth may be predisposed to develop adult BED and obesity.…”
Section: Reward Responsivitymentioning
confidence: 99%
“…A possible way physical activity may affect eating behaviors is through cognitive processes that are related to food intake. Neuroimaging studies provide quantitative measurements of neural correlates of appetite and food intake (English et al., 2019; Hollman et al., 2012; Holsen et al., 2005; Masterson et al., 2018). For example, studies using functional magnetic resonance imaging (fMRI) report that acute bouts of physical activity reduce neural responses to images of food in reward regions of the brain and increases activity to high‐calorie, compared to low‐calorie, images potentially suggesting increased inhibition or food‐related cognitive control (Evero et al., 2012; Masterson et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, inconsistencies may be the result of differences in questionnaire format. Future longitudinal designs should assess whether youth who report LOC‐eating presence on the LOC‐ED‐Q are at heightened risk for weight gain or metabolic complications, compared with those who report LOC‐eating on the QEWP‐C‐5, and to elucidate previously observed differences in outcomes based on LOC‐eating presence as reported on the LOC‐ED‐Q (English et al, ; Mazzeo et al, ). Consistent with hypotheses, all three measures were associated with greater depressive and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Constructs assessed by the LOC‐ED‐Q were based on a multisite study that elucidated the behavioral, contextual and emotional correlates of LOC‐eating (Tanofsky‐Kraff et al, ) in order to improve upon prior inadequate measures of LOC‐eating in youth. Two studies have used the LOC‐ED‐Q to assess the presence of LOC‐eating (English et al, ; Mazzeo et al, ). English et al () found that youth with LOC‐eating as identified by the LOC‐ED‐Q showed increased susceptibility to overeating in response to large portions, and using fMRI, found that such children showed greater cerebellar activation when responding to food cues compared with those who did not report LOC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation